Investigation of the Electrodeposited CoNiFe Alloy Coating on Microstructure and Mechanical Properties - Salleh, Z.; R. N. M. Masdek, N.; A. Kamarulbaharin, Z.; M Taib, Y.; Z. Abu, M. (International Journal of Engineering and Technology, 2018)
In recent years, intensive study has been conducted on ternary Co-Ni-Fe alloys because of their outstanding physical and chemical properties which are nearly close to hard chromium deposit. The CoNiFe coating is the most commonly produced by an electrodeposition method for its flexibility and easy manipulation of coating properties. Coating process acts as preventive action to corrosion problems which are one of the significant problems that can be related to the metal works. In the transportation sector such as rail transport, for instance, there is one vital part that is exposed to corrosion, and it causes a lot of negative results. Corrosion defect cost lots of money to replace the defected ones; however a functional coating which involves nanoparticles can be used to counter the problem.Â  The objective of this research is to recycle the used or corroded fastener by implementing a coating process could be a huge step in reducing the total cost and therefore, help to maintain the environment's sustainability. Throughout this research, Nanocrystalline CoNiFe alloys were electrodeposited in sulphate bath with several constant parameters. The electrodeposition method was done in 30 minutes with a current of 1.7A and was proven to slightly improve the surface morphology. CoNiFe elements were successfully identified with lumpy globular pattern grains and acceptable thickness. Through the hardness investigation, the coating produced the microhardness of 317.94 Hv which almost doubled up the non-coated hardness. Besides that, CoNiFe coating also exhibited a lower rate of wear, a coefficient of friction and frictional force compared to non-coated fastener.Â Â